P1271PARADOXICAL EFFECT OF ALDOSTERONE ON CARDIOVASCULAR OUTCOME IN MAINTENANCE HEMODIALYSIS PATIENTS. (6th June 2020) - Lee, Young-Ki; Choi, Sun Ryoung; Park, Hayne Cho; Kim, Do Hyoung; Cho, Ajin; Kim, Juhee; Yoon, Jong-Woo; Noh, Jung-Woo; Kang, Min-Kyung
Abstract: Background and Aims: Patients with end-stage renal disease have an increased risk of cardiovascular (CV) mortality and left ventricular diastolic dysfunction (LVDD) is known to contribute to its high occurrence. Although high serum aldosterone level is involved in the development of CV complications in general population, this association is unclear in patients undergoing hemodialysis (HD). We aimed to determine the impact of serum aldosterone on LVDD and CV mortality among HD patients. Method: We performed a prospective cohort study of maintenance HD patients without CV disease. Patients were divided into two groups according to the median level of serum aldosterone (44 ng/dL). All patients underwent echocardiography to evaluate diastolic dysfunction. Proportions of LVDD and CV mortality were compared between high and low aldosterone groups. Results: We enrolled a total of 60 adult patients (mean age 57.9±12.1 years, male 30.0%). Low aldosterone group had an increased left ventricular diastolic dimension compared with high aldosterone group (52.2±8.4 vs. 50.3±5.2 mm, p=0.033). The E/è ratio (19.5±7.5 vs. 14.6±5.2, p=0.024) was significantly higher among patients in low aldosterone group compared to high aldosterone group. There were no significant differences either in ejection fraction, LVMI, or the proportion of LVH between two groups. Low log-aldosterone (odds ratio 0.403; 95% confidence interval 0.188-0.862) and large left atrial dimension (1.308; 1.114-1.536) were independent risk factors for LVDD. In addition, cox regression analysis demonstrated that low log-aldosterone was an independent predictor of CV mortality in HD patients (hazard ratio 0.505; 95% confidence interval 0.294-0.869, p=0.014). Conclusion: Low serum aldosterone was not only associated with LVDD but also an independent predictor of CV mortality among HD patients.